2011
DOI: 10.1289/ehp.1002429
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic and Childhood Leukemia: The ESCALE Study (SFCE)

Abstract: BackgroundTraffic is a source of environmental exposures, including benzene, which may be related to childhood leukemia.ObjectivesA national registry–based case–control study [ESCALE (Etude Sur les Cancers et les Leucémies de l’Enfant, Study on Environmental and Genetic Risk Factors of Childhood Cancers and Leukemia)] carried out in France was used to assess the effect of exposure to road traffic exhaust fumes on the risk of childhood leukemia.MethodsOver the study period, 2003–2004, 763 cases and 1,681 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 35 publications
6
69
1
2
Order By: Relevance
“…Our study in the context of previous studies 12 Our results are consistent with the findings of some but not all previous studies of childhood cancer and residence in the proximity to highly trafficked roads [9,[24][25][26][27][28]. The largest of these studies, based on over 700 cases of ALL, found a doubling of the risk among children living within 500 m of high-speed highways and main roads compared to unexposed children [9].…”
Section: Main Findingssupporting
confidence: 92%
See 3 more Smart Citations
“…Our study in the context of previous studies 12 Our results are consistent with the findings of some but not all previous studies of childhood cancer and residence in the proximity to highly trafficked roads [9,[24][25][26][27][28]. The largest of these studies, based on over 700 cases of ALL, found a doubling of the risk among children living within 500 m of high-speed highways and main roads compared to unexposed children [9].…”
Section: Main Findingssupporting
confidence: 92%
“…The largest of these studies, based on over 700 cases of ALL, found a doubling of the risk among children living within 500 m of high-speed highways and main roads compared to unexposed children [9]. Other studies using proximity measures found little support for an association with leukaemia risk [12,[29][30][31][32].…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Há estudos também que relataram associação estatisticamente significante entre proximidade residencial com áreas de alta intensidade de tráfego e ocorrência de cânceres do sistema hematológico (Boothe and Shendell 2008;Amigou et al 2011;Spycher et al 2015).…”
Section: Introductionunclassified